Tourism Market and Demographic Changes - Alexandru Nedelea (Contemporary Economics)
This paper identifies the major demographic trends and their implications for consumer market. It is important to know how will demographic change influence the tourism market in particularly and how can the tourist industry adapt to these. The advancing ageing of society will result in far reaching changes, particularly on the demand side. To profitably seize the opportunities, managers must understand how senior markets evolve and adapt products and service offerings along multiple dimensions to meet the needs of senior consumers.